Protective effects of aucubin on osteoarthritic chondrocyte model induced by hydrogen peroxide and mechanical stimulus. Issue 1 (December 2017) - Young, In-Chi; Chuang, Sung-Ting; Hsu, Chia-Hsien; Sun, Yu-Jun; Liu, Hwa-Chang; Chen, Yo-Shen; Lin, Feng-Huei
Abstract Background During the onset of osteoarthritis (OA), certain biochemical events have been shown to accelerate cartilage degradation, including the dysregulation of cartilage ECM anabolism, abnormal generation of reactive oxygen species (ROS) and overproduction of proteolytic enzymes and inflammatory cytokines. The potency of aucubin in protecting cellular components against oxidative stress, inflammation and apoptosis effects are well documented, which makes it a potential candidate for OA treatment. In this study, we aimed to evaluate the protective benefits of aucubin against OA using H2 O2 and compression induced OA-like chondrocyte models. Methods The effects of aucubin were studied in porcine chondrocytes after 1 mM H2 O2 stimulation for 30 min or sustained compression for 24 h. Effects of aucubin on cell proliferation and cytotoxicity of chondrocytes were measured with WST-1 and LDH assays. ROS production was evaluated by the Total ROS/Superoxide Detection Kit. Caspase-3 activity was evaluated by the CaspACE assay system. The levels of apoptosis were evaluated by the Annexin V-FITC apoptosis detection kit. OA-related gene expression was measured by reverse transcription quantitative polymerase chain reaction (RT-qPCR). Total DNA quantification was evaluated by the DNeasy Blood and Tissue kit. Sulfated-glycosaminoglycans (sGAGs) production and content were evaluated by DMMB assay and Alcian blue staining. Results The results showed that the ROS scavenge effects of aucubin appeared after 1 h of pretreatment. Aucubin could reduce the caspase-3 activity induced by H2 O2, and reduced the apoptosis cell population in flowcytometry. In RT-qPCR results, aucubin could maintain ACAN and COL2A1 gene expressions, and prevent IL6 and MMP13 gene up-regulation induced by H2 O2 and compression stimulations. In the DMMB assay and Alcian blue staining, aucubin could maintain the sGAG content and protect chondrocytes against compressive stress, but not oxidative stress from H2 O2 . Conclusions These results indicated that aucubin has protective effects in an osteoarthritic chondrocyte model induced by H2 O2 and mechanical stimulus.